Desempenho e parâmetros intestinais de frangos de corte alimentados com rações contendo óleos de copaíba e sucupira - Noleto, Raiana Almeida (2014)
Two experiments were conducted with the objective of evaluating Copaiba and Sucupira oils as an antimicrobial additive in broiler feed with low challenge. In Experiment 1, 600 one-day-old male chicks, Cobb500, were housed in boxes with reused litter. The design was completely randomized with four treatments (feed without additives; feed with avilamycin; feed with Copaiba oil and feed with Sucupira oil), with six replicates of 25 poultries each. Performance was evaluated and at 40 days of age intestine was collected to biometrics and histomorphometry. In Experiment 2, 360 Cobb500 male chicks were housed in batteries. The design was in randomized blocks, with the blocked sex, with five treatments (nonchallenged poultries group fed without additives and groups of challenged poultries fed without additives; diet with avilamycin; diet with Sucupira oil and diet with Copaiba oil), with six replicates of 12 poultries each. The challenge was performed with the crop inoculation of 0.5 ml of sterile saline 0.85% containing 2.7 x 10 6 CFU / mL Salmonella Enteritidis. Performance and feed metabolization nutrients coefficient have been reported. Biometrics of the intestine, liver, spleen and bursa of Fabricius and histomorphometry of the intestine were evaluated at 14 and 35 days. Salmonella Enteritidis research was performed in fragments of spleen and liver at 14 days of age and spleen, liver and cecal tonsils at 35 days of age and weekly in cloacal swabs. Performance data, feed nutrients metabolization, histomorphometry and biometry of the organs were subjected to variance analysis and averages were compared by Tukey test (5%). For the Salmonella Enteritidis research simple frequency (percentage) was applied. In Experiment 1 the addition of 0.5g/kg diet, the Sucupira oil worsened performance compared to other treatments, and the addition of 2g/kg diet of Copaiba oil, and use of avilamycin did not influence performance. The intestinal growth was not influenced by the addition of additives. In Experiment 2 at 21 days of age, the addition of Sucupira oil resulted in worse performance compared to the group without challenge fed diets without additives. At 28 days of age, Sucupira oil worsened performance for the groups without additive and with antibiotic. The addition of Copaiba did not improve broiler performance. Metabolism of dry matter and ethereal extract, and nitrogen retention and ethereal extract in the group fed with the diet with inclusion of Copaiba or Sucupira oils were similar to groups with antibiotics, however, Sucupira oil promoted nitrogen metabolism reduction. Diets containing Copaiba oil or Sucupira oil promoted weight of spleen and bursa of Fabricius similar to that obtained with diets containing antibiotic. The inclusion of the Copaiba oil did not improve intestinal development, yet inclusion of Sucupira promoted greater duodenum villus height compared to the group receiving avilamycin at 35 days old. There was a lower Salmonella Enteritidis isolation frequency in the spleen and cloacal swabs with the addition of Copaiba oil in relation to the antibiotic group and the group with Sucupira oil. This Sucupira oil dosage is not recommended, since it impairs performance, and Copaiba oil did not promote improvements.